MENELISIK PROGRAMPEMBANGUNAN NASIONAL DI ERA PEMERINTAHAN SOEHARTO - Mayrudin, Yeby Ma’asan (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2018)
This article discusses the issue of the policies of the New Order government's national development program based on concepts that are firmly held and always socialized and doctrined during his reign, namely the Trilogy of Development concept, which consists of three key points, namely development equality, economic growth, and national stability. four main policies, namely macroeconomic policy, economic structure reform policy, population policy, and political stability policy.